2014
DOI: 10.1016/j.ijfoodmicro.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impact of Fusarium head blight pathogens and mycotoxins on malting barley quality in UK

Abstract: Fusarium head blight (FHB) caused by Fusarium and Microdochium species can significantly affect the yield of barley grain as well as the quality and safety of malt and beer. The present study provides new knowledge on the impacts of the FHB pathogen complex on the malting and brewing quality parameters of naturally infected barley. Quantitative real-time PCR and liquid chromatography double mass spectrometry were used to quantify the predominant FHB pathogens and Fusarium mycotoxins, respectively, in commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
94
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(114 citation statements)
references
References 49 publications
8
94
0
12
Order By: Relevance
“…Deoxynivalenol (DON), commonly produced by F. graminearum, is one of the principal quality problems of malting barley (27). Recently, Nielsen et al (25) demonstrated that F. poae affects malting and brewing parameters, and that F. poae DNA showed a significant positive relationship with NIV. However, specific studies on the effect of NIV on beer are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxynivalenol (DON), commonly produced by F. graminearum, is one of the principal quality problems of malting barley (27). Recently, Nielsen et al (25) demonstrated that F. poae affects malting and brewing parameters, and that F. poae DNA showed a significant positive relationship with NIV. However, specific studies on the effect of NIV on beer are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The ascomycete F. graminearum has major economic impact in the agriculture industry [52]. In general, the control of Fusarium spp has become challenging; for example azole, one of the available fungicides, is only moderately effective against F. graminearum [53].…”
Section: Discussionmentioning
confidence: 99%
“…These pathogens are responsible for quantitative damages, with significant yield losses (Hollaway et al 2013, Nielsen et al 2014 and, in particular when they cause FHB, of qualitative damages, due to mycotoxin accumulation in the grains. In fact, these three Fusarium species are all able to biosynthesize mycotoxins, in particular deoxynivalenol (DON), belonging to the group B of trichothecenes (Bottalico andPerrone 2002, Xu andNicholson 2009).…”
Section: Manuscript Received December 2017mentioning
confidence: 99%
“…The epidemiology of FHB, especially on wheat, is well known Nicholson 2009, Scherm et al 2013) and symptom gravity is often associated with a high proliferation of Fusarium biomass and a significant accumulation of mycotoxins (Pancaldi et al 2010, Nielsen et al 2014. Conversely, for FCR, the relationship between symptom severity, fungal biomass and mycotoxin accumulation is still poorly understood, because Fusarium causal agents do not directly colonize the head.…”
Section: Manuscript Received December 2017mentioning
confidence: 99%
See 1 more Smart Citation